214 Occupational lifting and fetal death: findings from the Danish National Birth Cohort using a industry-job exposure matrix. (11th October 2013) - Mocevic, E M; Jørgensen,; Svendsen,; Frost,; Andersen, Nybo; Bonde,
Abstract : Objective: We have in an earlier prospective cohort study observed a moderately increased risk of miscarriage based upon self-reported information on occupational lifting. In this paper we aim to corroborate or refute this observation by application of a industry-job exposure matrix for pregnant women. Methods: For 68, 096 occupationally active women, who participated in the Danish National Birth Cohort, information on occupational lifting was collected by telephone interviews around gestational week 16. We established an industry-job exposure matrix (IJEM) by computing the industry and job specific mean values of the pregnant women's self-reported daily lifting activities while pregnant. Subsequently all women were assigned IJEM value for her industry and job. The associations between occupational lifting and early miscarriage (12 weeks or less), late miscarriage (13–21 weeks), and stillbirth (22 weeks or more) were analysed using Cox regression models with gestational age as the underlying time variable and adjustment for age, body mass index, parity, smoking and alcohol consumption. Results: We observed 2, 726 pregnancy losses in a cohort of 68, 096 pregnant women. We found no consistent associations between increased heavy lifting and pregnancy losses up to gestational week 21. However, for fetal death occurring after week 21 we found an increased risk among women lifting more than 200 kg/day (Hazard Ratio (HR) = 1.55; 95% Confidence Interval (CI): 1.03–2.35) compared to non-lifting women. After controlling for potential confounders, the result for stillbirths became insignificant, but the estimate did not change much (HR = 1.40; 95%CI: 0.92–2.14). Conclusion: The study corroborates earlier findings in the Danish National Birth Cohort that occupational lifting is related to an increased risk for fetal death. Due to the prospective design with late enrollment into the study, ascertainment of early miscarriage is incomplete and therefore the study does not provide strong evidence on risk for early miscarriage.